Penerimaan Teknologi Konferensi Video dan Motivasi Belajar - Triana Noermalia; Irwansyah Irwansyah (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
The Covid-19 pandemic that has hit all corners of the world including Indonesia is a phenomenon that has a major impact on all sectors of people's lives, including the education sector. Therefore, educational institutions immediately resolve this problem by implementing online lectures as a substitute for face-to-face lectures. However, student acceptance of video conferencing technology did not fully motivate students to undergo online classes. The purpose of this study was to describe student acceptance of video conferencing technology in distance learning during pandemic. Through the digital ethnography method, researchers will explore and obtain reflections on the experiences of students who use digital technology to carry out the learning process online through video conferencing technology. Data collection was carried out through interviews with four informants from four different departments and literature studies. Data analysis of student communication technology acceptance was carried out using the Technology Acceptance Model (TAM) which was adapted from Mayring's (2010) research. The results of the analysis of the interview data with four informants show that the acceptance of student technology is not the only factor that affects student motivation in running online lectures. Factors that also influence student motivation to run online courses include the demands of lectures, assignments given, and the learning system used when running online classes. Student motivation in running online lectures needs to be considered because it plays a role in their understanding of the material being studied. Pandemi Covid-19 yang melanda seluruh penjuru dunia termasuk Indonesia merupakan fenomena yang memiliki dampak besar pada seluruh sektor kehidupan masyarakat, tak terkecuali sektor pendidikan. Oleh sebab itu, instansi pendidikan dengan segera menuntaskan permasalahan ini dengan menerapkan kuliah online sebagai pengganti kuliah tatap muka. Namun, penerimaan mahasiswa terhadap teknologi konferensi video ternyata tidak sepenuhnya memotivasi mahasiswa dalam menjalani kelas online. Tujuan penelitian ini adalah untuk mendeskripsikan penerimaan mahasiswa terhadap teknologi konferensi video dalam pembelajaran jarak jauh di masa pandemi. Melalui metode etnografi digital, peneliti akan menggali hingga memperoleh refleksi dari pengalaman mahasiswa yang memanfaatkan teknologi digital untuk melakukan proses pembelajaran secara online melalui teknologi konferensi video. Pengumpulan data dilakukan melalui wawancara terhadap empat informan dari empat jurusan berbeda dan studi literatur. Analisis data penerimaan teknologi komunikasi mahasiswa dilakukan menggunakan Technology Acceptance Model (TAM) yang diadaptasi dari penelitian Mayring (2010). Hasil analisis dari data wawancara terhadap empat informan menunjukkan bahwa penerimaan teknologi mahasiswa tidak menjadi satu-satunya faktor yang mempengaruhi motivasi mahasiswa dalam menjalankan kuliah online. Faktor-faktor yang turut mempengaruhi motivasi mahasiswa menjalankan kuliah online di antaranya adalah tuntutan perkuliahan, tugas yang diberikan, serta sistem belajar yang digunakan saat menjalankan kelas online. Motivasi mahasiswa dalam menjalankan kuliah online perlu diperhatikan karena berperan dalam pemahamannya mengenai materi yang dipelajari.